2020
DOI: 10.5219/1329
|View full text |Cite
|
Sign up to set email alerts
|

The influence of honey enrichment with bee pollen or bee bread on the content of selected mineral components in multifloral honey

Abstract: Bee products, such as honey, pollen, and bee bread, are an excellent source of bioactive ingredients, including minerals, having a health-supporting effect. However, due to the specific sensory properties of bee pollen and bee bread, the best way to include them in a diet is to add them to honey. Therefore, the aim of this paper was to evaluate the influence of the added bee pollen or bee bread on selected minerals content in multifloral honey. The mineral content was analyzed using absorption atomic spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…According to the estimated results, adding bee bread or fermented pollen to honey can be enriched up to 10 times with selected elements, especially those classified as microelements. Multiple enrichment of honey with macroelements (K, Na, Ca, Mg) was previously confirmed by Habryka et al [10], who found the dependence of the content of these elements was on the share of the introduced additive, achieving the highest enrichment in magnesium (almost 25 times with a 25% addition of bee pollen and 20 times with a 25% addition of bee bread). In the case of the analyzed microelements (Fe, Zn, Cu, Mn), the same trend was also observed, and the highest degree of enrichment was observed for iron [10].…”
Section: Physicochemical Evaluationmentioning
confidence: 56%
See 3 more Smart Citations
“…According to the estimated results, adding bee bread or fermented pollen to honey can be enriched up to 10 times with selected elements, especially those classified as microelements. Multiple enrichment of honey with macroelements (K, Na, Ca, Mg) was previously confirmed by Habryka et al [10], who found the dependence of the content of these elements was on the share of the introduced additive, achieving the highest enrichment in magnesium (almost 25 times with a 25% addition of bee pollen and 20 times with a 25% addition of bee bread). In the case of the analyzed microelements (Fe, Zn, Cu, Mn), the same trend was also observed, and the highest degree of enrichment was observed for iron [10].…”
Section: Physicochemical Evaluationmentioning
confidence: 56%
“…Multiple enrichment of honey with macroelements (K, Na, Ca, Mg) was previously confirmed by Habryka et al [10], who found the dependence of the content of these elements was on the share of the introduced additive, achieving the highest enrichment in magnesium (almost 25 times with a 25% addition of bee pollen and 20 times with a 25% addition of bee bread). In the case of the analyzed microelements (Fe, Zn, Cu, Mn), the same trend was also observed, and the highest degree of enrichment was observed for iron [10]. This element is particularly important for human health, it is involved in many biochemical processes, including oxygen transport through the blood, DNA synthesis, and redox reactions.…”
Section: Physicochemical Evaluationmentioning
confidence: 56%
See 2 more Smart Citations
“…Based on the above, it can be concluded that flavoured honey is an increasingly popular product among consumers. Enriching honey with other healthy ingredients, such as spices, herbs, dried fruits, pollen, propolis, coumarin and spirulina, can be considered novel innovative food products [20,40,[74][75][76].…”
Section: Discussionmentioning
confidence: 99%